Trend of Hepatitis B Surface Antigen (HBsAg) among blood donors at the blood bank of a tertiary care referral teaching hospital in Southern India - A., Yashovardhan; K.V., Sreedhar Babu; D.S., Jothi Bai (International Journal of Research in Medical Sciences, 2017)
Background: Blood is a scarce, but lifesaving resource; it is also the most efficient vehicle for the transmission of Hepatitis B virus (HBV). Hence there is a need for accurate screening of hepatitis B surface antigen (HBsAg) among blood donors. The present study was designed to assess the seroprevalence of HBsAg, among the voluntary and replacement blood donors in the blood bank of a tertiary care referral teaching hospital in Andhra Pradesh. Methods: This is a prospective cross sectional analytical study conducted over a period of one and a half year. A total of 9909 donor blood samples were screened for HBsAg status using enzyme linked immunosorbent assay (ELISA). The reactive samples have been tested in duplicate using different kit. The samples reactive in all three times were considered positive. The samples which were reactive only in first test were labeled as false positive. Results: Out of 9909 blood donors screened, 255 (2.6%) were initially reactive and 219 (2.2%) were reactive after triple testing. Conclusions: Our study showed similar HBsAg seroprevalence as that reported by World Health Organization (WHO) statistics in intermediate zone. But there was a mild increase in HBsAg seroprevalence among donors belonging to rural areas in our region compared to the urban donors.